Character Education: Examining The Mental Revolution In The Context Of Islamic Education - Ahmad Muslim (Penerbit Hellow Pustaka, 2024)
Mental Revolution is interpreted as a change in mindset in national life. Mental revolution does not simply rely on good intentions, but must take into account structural changes in societal interactions. In the realm of Islamic education, mental revolution must consider the structure of meaning, domination and legitimacy. These three things condition the mindset of Islamic education practitioners, the Islamic Education System, and the structure of Islamic education institutions themselves. The orientation of change as a result of implementing the mental revolution must be shown in the form of improving educational services for the welfare of society. Islamic educational institutions are expected to be able to explain injustice, arbitrariness and make people look, feel, think and act more rationally and wisely.